2015
DOI: 10.1155/2015/465465
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol, Propofol-Remifentanil, and Propofol-Fentanyl Administrations with Each Other Used for the Sedation of Patients to Undergo ERCP

Abstract: Introduction. Using single anesthetic agent in endoscopic retrograde cholangiopancreatography (ERCP) may lead to inadequate analgesia and sedation. To achieve the adequate analgesia and sedation the single anesthetic agent doses must be increased which causes undesirable side effects. For avoiding high doses of single anesthetic agent nowadays combination with sedative agents is mostly a choice for analgesia and sedation for ERCP. Aim. The aim of this study is to investigate the effects of propofol alone, prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
3
19
1
3
Order By: Relevance
“…These findings were consistent with the literature. Similar findings are declared between the two groups in the many studies (Mulas et al,1998;Doyle et al,2001;Haytural, 2015, Monsef et al, 2019.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were consistent with the literature. Similar findings are declared between the two groups in the many studies (Mulas et al,1998;Doyle et al,2001;Haytural, 2015, Monsef et al, 2019.…”
Section: Discussionsupporting
confidence: 82%
“…In their study with 16 patients from the remifentanil and fentanyl groups, some authors reported that 7 patients in the remifentanil group and Comparison of the effects of Remifentanil and Fentanyl for day case surgery 4 patients in the fentanyl group had analgesic requirements in the early post-operative period (Doyle et al,2001). But the others found no difference VAS scores between fentanyl and remifentanil group in their studies (Haytural, 2015). On the other hand; some other authors found higher VAS scores in the fentanyl group (Monsef et al, 2019).We didn't administer additional analgesics in our study, but when the VAS scores were evaluated, it was concluded that pain control was better achieved in patients treated with fentanyl in the early period.…”
Section: Discussioncontrasting
confidence: 56%
“…The recovery time is a little longer in P group than in PR group accordingly due to a larger use of propofol. In Haytural et al's research in which the patients undergo endoscopic retrograde cholangiopancreatography (ERCP), patients in the propofol group need more propofol than the other groups using remifentanil and fentanyl along with propofol, which is the same like our study . Remifentanil decreases the doses of propofol and makes the recovery time shorter.…”
Section: Discussionsupporting
confidence: 70%
“…Haytural et al's research in which the patients undergo endoscopic retrograde cholangiopancreatography (ERCP), patients in the propofolgroup need more propofol than the other groups using remifentanil and fentanyl along with propofol, which is the same like our study 21. Remifentanil decreases the doses of propofol and makes the recovery time shorter.MR happens in 4 (8.2%) patients in PR group compared with 0 in P group.…”
supporting
confidence: 81%
“…Moderate sedation provides a low risk of serious adverse events with all currently available agents (2). Medication used in moderate sedation should have minimum side effects, it should depress the patient's consciousness level in a controlled manner, and it should have inactive metabolites, and should not necessitate resedation (3,4).…”
Section: Introductionmentioning
confidence: 99%